65‐1: Distinguished Paper: Photometric and Colorimetric Measurements of Near‐Eye Displays. Issue 1 (2nd June 2017) - Penczek, John; Boynton, Paul A.; Meyer, Frederick M.; Heft, Eric L.; Austin, Richard L.; Lianza, Thomas A.; Leibfried, Lukas V.; Gacy, Luca W.
Abstract : We discuss the optical system design concepts for properly measuring the photometric and colorimetric characteristics of near‐eye displays. Measurements on various near‐eye displays demonstrate the variance in instrument results due to their optical design. Based on these findings, optical instrument design guidance is given for the proper measurement of virtual image displays.